Pengaruh Variasi Fraksi Volume Filler Terhadap Kekuatan Mekanik Komposit Sandwich Polyester Serat Kenaf Core Styrofoam - Sentosa, Aman; Sumarji, Sumarji; Djumhariyanto, Dwi (ROTOR, 2015)
Composite sandwich reinforcementÂ  kenaf fiber polyester with Styrofoam core is an alternative material that has the potential to be developed as an application in various fields with an excess of nature that is strong, lightweight, rigid, able to withstand bending loads, impact, vibration damping and sound. This study is intended to overcome the problems of fishermen Muncar - Banyuwangi in the selection of materials manufacture of safe fish robust and insulated to preserve or maintain the freshness of the fish catch of fishermen low temperature. This study was conducted to determine the effect of variations in fiber volume fraction of the increase in impact strength and bending composite materials sandwich.Untuk get impact strength values ââusing the tool impact test with a maximum capacity of 300 joules specifications, pendulum mass of 20.9 kg, 0.83 m long pendulum arm, while to obtain bending strength values ââusing a universal testing machine capacity of 300 KN. Variations were used in this study is the percentage of fiber volume fraction of 10% fiber, 20%, 30%, and 40%. The results showed that the variation of fiber volume fraction of 40% had values ââhigher impact strength and bending of 0.30 Joules / mmÂ² and 5,65MPa than the fiber volume fraction of 10% has impact and bending strength values ââwere lower at 0.14 joules / mm2 and 0.30 MPa. So in this study limits the variation of fiber volume fraction of 10% to 40% proved that if the greater the percentage of fiber volume fraction value will increase the value of impact strength and bending in composite sandwich. Keywords: fiber volume fraction, impact strength and bending, composite sandwich